Tourism Development Analysis on Utilization Optimization of Koto Panjang Reservoir in Kampar Regency, Riau Province - Cemda, Abdul Rahman (Nusantara Science and Technology Proceedings, 2021)
Optimization is a process carried out in order to achieve good results, this is certainly very important in development efforts, one of which is development in the tourism sector. Tourism objects will not attract visitors if the development of their use is not carried out optimally. One of the tourism places that has become a concern in optimizing its benefits is tourism of the Koto Panjang reservoir located in Kampar Regency, Riau Province. This study aims to determine the process of tourism development towards optimizing the utilization of the Koto Panjang reservoir. The research method used in this study is quantitative research, using questionnaires, interviews and observation data collection methods. Analysis of the data used in this study using Structural Equation Modeling (SEM) with the SmartPLS 3.0 tool. The results of the study show that tourism development on utilization optimization shows a negative effect.